Management Curriculum 2013 in the Framework of Improving the Quality of Education in Islamic Junior High School 2 Ponorogo - Saepul Anwar; M. J. M. Khadafi (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
Education is one of the main factors in making humans a quality and innovative human being. Because humans are required to always do innovation and renewal and have better knowledge, creativity and life skills. In the field of education, the role of management is very important in determining the quality of an educational institution especially curriculum management. From the above background the authors formulated the title